Technical Perspective: A compiler's story. - Morrisett, Greg (Communications of the ACM, 2009)
The article discusses the means by which computer scientists verify that computer programs are without error, without bugs, proven correct, and formally verified. It references the article "Formal Verification of a Realistic Compiler," by Xavier Leroy in the same issue. Also discussed are computer compilers and industry concerns with security and reliability.